Pengaruh Penerapan Etika Bisnis Terhadap Kinerja Karyawan di CV. Mufidah - Nadia Putri Randio; Usman Moonti; Roy Hasiru; Radia Hafid; Ardiansyah Ardiansyah; Rierind Koniyo (Journal of Economic and Business Education, 2023)
This present study to determine the effect of applying bussines ethics on employees’ at CV. Mufidah. Gorontalo City. This study employed a quantitative approach with a survey research method. The data used were primary data obtained by distributing questionaires to employees of     CV. Mufidah, Gorontalo City in 2022. Additionally, the number of samples in this study was 30 respondents, while the data analysis tecnique was simple linear regression. The finding of the study revealed that applying business ethics affected employees’ performance at CV. Mufidah, Gorontalo City by 70,9%, while the remaining 29,1% were affected by other variebles were not examined in this study